Cryptic subarctic diversity: a new bumblebee species from the Yukon and Alaska (Hymenoptera: Apidae). Issue 45 (9th December 2016) - Williams, Paul H.; Cannings, Sydney G.; Sheffield, Cory S.
ABSTRACT: It is nearly 90 years since a bumblebee species has been described for the first time from Canada or the USA that was previously unrecognised by science. We describe and illustrate Bombus ( Alpinobombus ) kluanensis sp. nov. and begin to map its distribution. This species was discovered through analysis of Cytochrome c Oxidase subunit I barcodes and had been unsuspected on the basis of morphological and colour characteristics. So far, 247 female specimens considered to belong to this species are known from the subarctic mountains associated with the Denali Fault running from the Alaska Range (Alaska, USA) to Kluane in the Saint Elias Mountains (Yukon, Canada). A checklist of all species of the subgenus Alpinobombus worldwide is provided. http://zoobank.org/urn:lsid:zoobank.org:pub:78D524DD-FFBA-4BC4-8D39-3EF4F6BDD39E